Moisture generator and preparation method thereof
Through the design of MOF-303 and BC composite film and asymmetric electrode, the problems of low current density and poor environmental adaptability of the moisture generator are solved, and efficient and low-cost moisture power generation performance is achieved, and stable power generation is adapted to a wide humidity range.
Patent Information
- Application Number
- CN202510513190.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-23
- Publication Date
- 2025-09-05
AI Technical Summary
The existing moisture generators have limitations such as low current density, poor environmental adaptability, difficulty in miniaturization and flexibility, and the preparation process of porous polyurethane foam is complex and has high cost, making the channel structure difficult to regulate, affecting performance.
The BC composite membrane of MOF-303 and bacterial cellulose is combined with lithium chloride solution impregnation and asymmetric electrodes to form a sandwich structure moisture generator. The porous material of MOF-303 and the nanostructure of BC are enhanced. The synergistic effect of PAN/PVDF membrane is used to achieve directional migration and evaporation of water molecules, and the asymmetric electrode drives ion migration to generate charge difference.
It realizes stable power generation in a wide humidity range, improves current density and environmental adaptability, reduces preparation costs, and improves the stability and flexibility of the device.
Smart Images

Figure CN120601771A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of wet gas power generation, and in particular to a wet gas generator and a preparation method thereof. Background Art
[0002] As the energy crisis intensifies, the development of green renewable energy technologies has become an urgent need. Currently, a variety of new green energy conversion devices have been developed, such as solar cells, triboelectric nanogenerators, and moisture generators.
[0003] Moisture, one of the most abundant resources in the environment, has long been overlooked for its inherent energy. Wet gas power generation, an effective way to convert potential energy into electricity through the hygroelectric effect, can infinitely recycle and recycle atmospheric water. It offers advantages such as environmental friendliness, simple structure, direct current generation, and the absence of external rectification circuits. However, existing wet gas generators face limitations such as low current density, poor environmental adaptability, and difficulty in miniaturization and flexibility, limiting their application scope. For example, patent CN116247969A provides a polymer wet gas generator based on a porous support, a preparation method, and an application. The wet gas generator is composed of a positive and negative electrode and an active layer. The active layer is composed of a composite of porous polyurethane foam and polystyrene sulfonic acid solution. The negative electrode is an active electrode aluminum mesh, and the positive electrode is conductive glass. The wet gas generator can obtain energy from air moisture and convert it into electrical energy under relatively wide humidity conditions. Its principle is to utilize the hydrovoltaic effect. Moisture moves directionally along the humidity gradient inside the composite material, and charge separation and movement are generated on the microscopic surface where the material contacts moisture, thereby showing electrical output on both sides with humidity difference. The porous characteristics of the composite material ensure the output stability of the moisture circulation path and device performance. However, the preparation process of the porous polyurethane foam in this technical solution is complex and costly, and the pore structure of the porous polyurethane foam is difficult to effectively control, which to a certain extent affects the performance of the wet gas generator. Summary of the Invention
[0004] Technical problems to be solved: In response to the technical problems existing in the prior art wet gas generator, the present invention provides a wet gas generator and a preparation method thereof, which has the advantages of high efficiency and low cost by improving the hygroscopic material and structural design.
[0005] Technical solution: The method for preparing a wet gas generator according to the present invention comprises the following steps: Step 1: MOF-303 and bacterial cellulose BC were mixed in a mass ratio of 1:(5-11), and the first composite membrane was obtained by vacuum filtration and drying; Step 2: Immersing the first composite membrane in a lithium chloride solution with a concentration of 5-30%, and drying the solution after immersion to obtain a second composite membrane; Step 3: placing a polyacrylonitrile (PAN) membrane and a polyvinylidene fluoride (PVDF) membrane on the upper layer of the second composite membrane in sequence to obtain a third composite membrane; Step 4: placing the third composite membrane on a waterproof and breathable non-woven fabric, and combining it with an asymmetric electrode to form a sandwich structure, wherein the asymmetric electrode is an aluminum electrode as a cathode and carbon paper as an anode, and encapsulating to obtain a moisture generator.
[0006] Preferably, the mass ratio of MOF-303 to BC in step 1 is 1:5, 1:7, 1:9, or 1:11.
[0007] Preferably, the mixing conditions in step 1 are: processing in a high-speed shearing machine with a rotation speed of 600-800 rpm; drying temperature of 60° C., and drying time of 30 min.
[0008] Preferably, the concentration of the lithium chloride solution in step 2 is 5%, 10%, 15%, 20%, or 30%.
[0009] Preferably, in step 2, the first composite membrane is immersed in the lithium chloride solution for 30 minutes, and the drying temperature is 60° C. and the drying time is 30 minutes.
[0010] Preferably, the fiber diameter of the PAN membrane and the PVDF membrane in step 3 is 500-2000 nm, and they are prepared by electrospinning.
[0011] Preferably, the moisture generator formed after packaging with the waterproof and breathable non-woven fabric in step 4 can generate electricity stably within a humidity range of 20% to 90% RH.
[0012] The present invention discloses a wet gas generator, comprising: The moisture absorption layer is composed of MOF-303 / BC / LiCl composite membrane; Diffusion layer, composed of PAN film; Moisture-wicking layer, composed of PVDF membrane; Asymmetric electrode, consisting of aluminum electrode and carbon electrode; The moisture absorption layer, the diffusion layer, and the moisture discharge layer are stacked in sequence and packaged by an asymmetric electrode and a waterproof and moisture-permeable non-woven fabric.
[0013] Preferably, the loading amount of lithium chloride in the hygroscopic layer is 5-20% of the mass of the composite membrane after impregnation.
[0014] Preferably, the moisture generator outputs different currents and voltages at different humidity levels.
[0015] Compared with the prior art, the present invention achieves the following technical effects: 1. The wet gas generator of the present invention uses a porous, highly hygroscopic, and structurally stable metal-organic framework (MOF-303). The metal ions and organic ligands of MOF-303 form a porous material. MOF-303's rich micro-nanopore structure enhances the adsorption of water molecules. BC is used as a carrier. BC has a unique woven structure and, due to its "nano effect," exhibits high water absorption and retention, high permeability to liquids and gases, high wet strength, and an ultra-fine network structure. The high specific surface area of MOF-303 combined with the nanostructure of BC enhances its moisture absorption capacity and efficiency. 2. In this wet gas generator, MOF-303 is compounded with BC and then impregnated with lithium chloride solution to obtain a MOF-303 / BC / LiCl composite membrane, which can enhance the moisture absorption capacity of the hygroscopic layer. The lithium chloride solution enhances the ion concentration difference, which can optimize the moisture transport path of the PAN / PVDF membrane. The PAN membrane and PVDF membrane work synergistically to achieve the diffusion and evaporation of water molecules under the action of the gradually decreasing pore size of the PAN and PVDF fiber membranes, thereby achieving directional migration and evaporation of water. Using asymmetric electrodes, the aluminum electrode and carbon paper form a redox reaction, driving ion migration, generating a continuous charge difference, and realizing stable and continuous wet gas power generation. The sandwich structure packaging ensures the stability and environmental adaptability of the device, and can generate electricity in a wide humidity range (20-90%RH). BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is a schematic diagram of the assembly structure of the wet gas generator of the present invention; Figure 2 These are electron microscope images of BC, MOF-303 / BC, and MOF-303 / BC / LiCl of the present invention; Figure 3 The moisture absorption diagram of MOF-303 / BC at different mass ratios under relative humidity of 50% rh; Figure 4 The moisture absorption diagram of MOF-303 / BC at different mass ratios under relative humidity of 60% rh; Figure 5 This is a line graph showing the mass change of MOF-303 / BC when it is immersed in lithium chloride solutions of different concentrations as the drying time changes; Figure 6 This is a line graph of moisture absorption rate of MOF-303 / BC after being immersed in lithium chloride solutions of different concentrations at 60% RH and 20°C; Figure 7 This is a line graph of moisture absorption rate of MOF-303 / BC after being immersed in different chloride salt solutions at 60% RH and 20°C; Figure 8 This is a performance comparison chart of a wet gas generator using a 20% LiCl / PAN / PVDF assembly method at a relative humidity of 50% RH. Figure 9 This is a performance comparison chart of a wet gas generator assembled using 20% LiCl / PVDF at a relative humidity of 50% RH. Figure 10 This is a performance comparison chart of a wet gas generator using a 20% LiCl / PAN assembly method at a relative humidity of 60% RH and 20°C. Figure 11 This is a comparison chart of the output voltage of the wet gas generator with different electrode combinations under the conditions of 60% RH, 20°C, and 20% LiCl; Figure 12 This is a comparison chart of the output current of the wet gas generator with different electrode combinations under the conditions of 60% relative humidity, 20℃, and 20% LiCl.
[0017] Reference numerals: 1. Moisture-absorbing layer; 2. Diffusion layer; 3. Moisture-discharging layer; 4. Aluminum electrode; 5. Carbon electrode; 6. Waterproof and breathable non-woven fabric. DETAILED DESCRIPTION
[0018] To make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the following Figures 1-12 The technical solutions of the embodiments of the present invention are clearly and completely described. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the described embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field are within the scope of protection of the present invention.
[0019] like Figure 1 As shown, the present invention discloses a moisture generator, including a moisture absorption layer 1, a diffusion layer 2, a moisture removal layer 3 and an asymmetric electrode, wherein the moisture absorption layer 1 is composed of a MOF-303 / BC / LiCl composite membrane; the diffusion layer 2 is composed of a PAN membrane; the moisture removal layer 3 is composed of a PVDF membrane; the asymmetric electrode is composed of an aluminum electrode 4 and a carbon electrode 5; the moisture absorption layer 1, the diffusion layer 2, and the moisture removal layer 3 are stacked in sequence and encapsulated by the asymmetric electrode and a waterproof and breathable non-woven fabric 6 to form a moisture absorption generator; wherein the loading amount of lithium chloride in the moisture absorption layer 1 is 5-20% of the mass of the composite membrane after impregnation.
[0020] The present invention also discloses a method for preparing a wet gas generator, comprising the following steps: Step 1: MOF-303 and bacterial cellulose (BC) were mixed in a mass ratio of 1:(5-11), and a first composite membrane was obtained by vacuum filtration and drying. The mass ratio of MOF-303 to BC can be selected as 1:5, 1:7, 1:9, or 1:11. The mixing conditions were as follows: treatment in a high-speed shearing machine at a speed of 600-800 rpm; drying temperature was 60°C, and drying time was 30 min.
[0021] Step 2: Immerse the first composite membrane in a lithium chloride solution with a concentration of 5-30%, and dry it after immersion to obtain a second composite membrane; wherein the concentration of the lithium chloride solution can be selected from 5%, 10%, 15%, 20%, and 30%; the first composite membrane is immersed in the lithium chloride solution for 30 minutes, and the drying temperature is 60°C and the drying time is 30 minutes.
[0022] Step 3: Place polyacrylonitrile (PAN) membrane and polyvinylidene fluoride (PVDF) membrane on the upper layer of the second composite membrane to obtain a third composite membrane. The specific preparation methods of the PAN membrane and PVDF membrane are as follows: 15% by mass of PAN is dissolved in DMF at 60°C, the electrospinning voltage is 20kV, the receiving distance is 15cm, and the forward speed is 1ml / h; 12% by mass of PVDF is dissolved in DMF and acetone, the DMF:acetone volume ratio is 6:4, and stirred in a heat-collecting constant temperature heating magnetic stirrer at 65°C until clear (generally 2h), and the electrospinning voltage is 16kV and the spinning speed is 0.017mL / min. The above electrospinning process is used to obtain PAN and PVDF nanofiber membranes with fiber diameters of 500~2000nm.
[0023] Step 4: The third composite membrane is placed on a waterproof, breathable nonwoven fabric and combined with an asymmetric electrode to form a sandwich structure. The asymmetric electrode comprises an aluminum electrode as the cathode and a carbon paper as the anode. The resulting moisture generator is packaged with the waterproof, breathable nonwoven fabric to produce stable power within a humidity range of 20% to 90%.
[0024] The performance of the wet gas generator provided by the present invention will be described in detail below with reference to specific embodiments.
[0025] Example 1: 2g of BC with a dry solids content of 1.3% was weighed, and 0.4g of MOF-303 was weighed at a MOF-303:BC mass ratio of 1:5. The mixture was sheared in a high-speed shearing machine at 650 rpm for 25 minutes to break up and mix into a flocculent layer. The mixture was then vacuum filtered to obtain a MOF-303 / BC composite membrane, which was then dried in an oven at 60°C for 30 minutes. A 20% lithium chloride solution was prepared and the MOF-303 / BC composite membrane was immersed in the lithium chloride solution for 30 minutes. After sufficient immersion, the membrane was dried in an oven at 60°C for 30 minutes to obtain a MOF-303 / BC / LiCl composite membrane. A PAN membrane (diffusion layer) and a PVDF membrane (evaporation layer) were sequentially placed on top of the MOF-303 / BC / LiCl composite membrane (hygroscopic layer) to obtain a third composite membrane. This third composite membrane was then placed on a waterproof and breathable nonwoven fabric and combined with the asymmetric electrodes to form a sandwich-structured moisture generator.
[0026] Example 2: 2g of BC with a dry solids content of 1.3% was weighed, and 0.286g of MOF-303 was weighed at a MOF-303:BC mass ratio of 1:7. The mixture was sheared at 650 rpm for 25 minutes to break up and mix into a flocculent layer. The mixture was then vacuum filtered to obtain a MOF-303 / BC composite membrane, which was then dried in an oven at 60°C for 30 minutes. A 20% lithium chloride solution was prepared and the MOF-303 / BC composite membrane was immersed in the lithium chloride solution for 30 minutes. After sufficient immersion, the membrane was dried in an oven at 60°C for 30 minutes to obtain a MOF-303 / BC / LiCl composite membrane. A PAN membrane (diffusion layer) and a PVDF membrane (evaporation layer) were sequentially placed on top of the MOF-303 / BC / LiCl composite membrane (hygroscopic layer) to obtain a third composite membrane. This third composite membrane was then placed on a waterproof and breathable nonwoven fabric and combined with the asymmetric electrodes to form a sandwich-structured moisture generator.
[0027] Example 3: 2g of BC with a dry solids content of 1.3% was weighed, and 0.222g of MOF-303 was weighed at a MOF-303:BC mass ratio of 1:9. The mixture was sheared at 650 rpm for 25 minutes to break up and mix into a flocculent layer. The mixture was then vacuum filtered to obtain a MOF-303 / BC composite membrane, which was then dried in an oven at 60°C for 30 minutes. A 20% lithium chloride solution was prepared and the MOF-303 / BC composite membrane was immersed in the lithium chloride solution for 30 minutes. After sufficient immersion, the membrane was dried in an oven at 60°C for 30 minutes to obtain a MOF-303 / BC / LiCl composite membrane. A PAN membrane (diffusion layer) and a PVDF membrane (evaporation layer) were sequentially placed on top of the MOF-303 / BC / LiCl composite membrane (hygroscopic layer) to obtain a third composite membrane. This third composite membrane was then placed on a waterproof and breathable nonwoven fabric and combined with the asymmetric electrodes to form a sandwich-structured moisture generator.
[0028] Example 4: First, 2g of BC with a dry solids content of 1.3% was taken, and 0.182g of MOF-303 was weighed at a MOF-303:BC mass ratio of 1:11. The mixture was sheared in a high-speed shearing machine at 650 rpm for at least 20 minutes to break up and mix into a flocculent layer. The mixture was then vacuum filtered to obtain a MOF-303 / BC composite membrane, which was then dried in an oven at 60°C for 30 minutes. A 20% lithium chloride solution was prepared and the MOF-303 / BC composite membrane was immersed in the lithium chloride solution for 30 minutes. After sufficient immersion, the membrane was dried in an oven at 60°C for 30 minutes to obtain a MOF-303 / BC / LiCl composite membrane. A PAN membrane as a diffusion layer and a PVDF membrane as an evaporation layer were sequentially placed on top of the MOF-303 / BC / LiCl composite membrane as a moisture absorption layer to obtain a third composite membrane. This third composite membrane was then placed on a waterproof and breathable nonwoven fabric and combined with the asymmetric electrodes to form a sandwich-structured moisture generator.
[0029] It should be noted that the concentration of the lithium chloride solution in the embodiment of the present invention can be selected from 5%, 10%, 15%, and 30% according to needs.
[0030] Comparative Example 1: The difference from Example 1 is that MOF-303 and BC are not composited.
[0031] Comparative Example 2: The difference from Example 2 is that the MOF-303 / BC composite membrane is not impregnated with LiCl salt solution and the MOF-303 / BC composite membrane is impregnated with other different hygroscopic salts. The corresponding moisture absorption results are as follows: Figure 7 As shown, the hygroscopic salts are 20% concentration of calcium chloride solution, potassium chloride solution, magnesium chloride solution and sodium chloride solution respectively.
[0032] Comparative Example 3: The difference from Example 3 is that different methods are used to combine the wet gas generators, that is, the continuous output performance of the wet gas generator containing only PAN layer or PVDF layer is observed. Figures 8-10 As shown, the combinations include 20% LICl / PAN / PVDF, 20% LICl / PVDF, and 20% LICl / PAN.
[0033] Comparative Example 4: The difference from Example 4 is that different electrode combinations are used to observe the output performance of the wet gas generator. Figure 11-12 As shown, the electrode material combinations include Al-C, Cu-C, Al-Al, Al-Cu, and Cu-Cu.
[0034] The performance of the hygroscopic power generation prepared in Examples 1 to 4 and Comparative Examples 1 to 4 was tested.
[0035] Figure 2The electron microscope images of BC, MOF-303 / BC and MOF-303 / BC / LiCl of the present invention are shown below: Figure 1 From (a), we can see that the internal network structure of pure BC is compact and orderly, and the fiber diameter is uniform and straight. Figure 1 From (b), we can see that pure MOF-303 is cubic in shape with clear edges and uniform particle size. Figure 1 As shown in (c), after MOF-303 and BC were compounded, more MOF-303 particles were filled in the gaps between BC fibers, indicating that MOF-303 and BC were successfully compounded. To further verify the hygroscopic properties of MOF-303 / BC composite membranes, composite membranes prepared with BC:MOF-303=1:1, 1:2, 1:3, 1:5, 1:7, and 1:9 were placed in an 80°C vacuum oven and dried for 1 hour to ensure that the composite membranes remained dry before absorbing moisture. The mass of the dried sample was weighed as m1. Composite membranes with different mass ratios of BC:MOF-303 were placed in a humidity generator, and the mass of the BC:MOF-303 sample was weighed once every 1 hour of adsorption, and the mass was m1. x , then the hourly moisture absorption performance of BC:MOF-303 composite membrane can be calculated by the formula: .
[0036] Depend on Figure 3-Figure 4 It can be seen that when the relative humidity is 50%RH and 60%RH respectively, as the mass ratio of MOF-303 / BC continues to increase, the hygroscopicity of MOF-303 / BC also continues to increase. However, when the MOF-303 / BC mass ratio is increased to 1:11, the hygroscopicity of MOF-303 / BC decreases significantly. The reason may be that the MOF-303 particles are too filled in the gaps between BC fibers, resulting in blockage of the internal pores of the fibers, which is not conducive to the capture and movement of water molecules. Therefore, the optimal MOF-303 / BC mass ratio is 1:9.
[0037] Compared with other hygroscopic materials, MOF-303 / BC composite membrane has advantages in hygroscopic performance, but there are still some shortcomings; lithium chloride (LiCl) is a hygroscopic salt, and direct use usually has problems such as salt leakage, corrosion to equipment, and environmental pollution. In the embodiment of the present invention, the MOF-303 / BC composite membrane is immersed in a LiCl solution to enhance the hygroscopic performance of the MOF-303 / BC composite membrane. Before immersion, the MOF-303 / BC composite membrane is subjected to a drying pretreatment to avoid the adsorption of LiCl by the MOF-303 / BC composite membrane. After the MOF-303 / BC composite membrane is dried, it is weighed and recorded as m1, and then MOF-303 / BC is immersed in LiCl solutions of different concentrations. After the immersion is completed, it is dried in an oven and weighed and recorded at regular intervals. The mass of the MOF-303 / BC / LiCl composite membrane at this time is mx , until the mass is constant, the adsorption amount of LiCl under different LiCl concentrations at the same immersion time can be obtained, which can be calculated by the formula: .
[0038] Depend on Figure 5 It can be seen that as the LiCl concentration continues to increase, the LiCl content also continues to increase. After drying for 300 minutes, the mass of the MOF-303 / BC / LiCl composite membrane remains basically unchanged. At this time, the LiCl content is the highest when the concentration is 30%. In order to further verify whether the hygroscopic performance of the MOF-303 / BC / LiCl composite membrane is enhanced, the hygroscopic performance follows the same measurement operation method as above. It should be noted that the MOF-303 / BC / LiCl composite membrane must be kept dry before absorbing moisture to avoid affecting the adsorption performance later. Figure 6 It can be seen that under the conditions of relative humidity of 60% RH and temperature of 20°C, the MOF-303 / BC / LiCl composite membrane absorbs moisture after 12 hours. As the LiCl concentration continues to increase, the hygroscopicity of the MOF-303 / BC / LiCl composite membrane increases significantly, proving that immersing the MOF-303 / BC composite membrane in LiCl solution can enhance its hygroscopicity and increase its ability to absorb atmospheric air water. When the LiCl concentration is 30%, although the MOF-303 / BC / LiCl composite membrane has the highest LiCl content, its hygroscopicity is significantly reduced compared with 20% LiCl. This may be due to the excessive LiCl content causing excessive water to accumulate inside the MOF-303 / BC composite membrane, but the pores are blocked and cannot absorb more water molecules from the outside, resulting in a decrease in hygroscopic performance. In addition, the salt content of 30% LiCl concentration is too high, which is prone to deliquescence and leakage problems in subsequent use. Therefore, it is better to control the LiCl concentration of the MOF-303 / BC composite membrane to 20%. Figure 7 It can be seen that by comparing the effects of impregnation of LiCl with several other common hygroscopic salts (such as NaCl, MgCl2, KCl, and CaCl2) on hygroscopicity, the Li atom has the smallest radius among these hygroscopic salts, and LiCl has the strongest water absorption. Compared with several other hygroscopic salts at the same concentration, LiCl has the highest hygroscopic volume. Therefore, impregnation with LiCl salt solution is selected to enhance the hygroscopic performance of the hygroscopic layer.
[0039] Figures 8-10 The continuous electrical output performance diagram of the wet gas generator under the relative humidity of 60%RH and temperature of 20℃ using different combinations is shown in the figure. Figures 8-10It can be seen that there is no obvious difference in the voltage output of the wet gas generator containing PAN membrane and PVDF membrane, containing only PAN membrane, and containing only PVDF membrane, and the output voltage is between 1.0-1.1V; however, there is a significant difference in the current output. The current output of the wet gas generator containing PAN membrane and PVDF membrane is about 8μA, while the current output of the wet gas generator containing only PAN membrane is about 2.5μA. Similarly, the current output of the wet gas generator containing only PVDF membrane is about 3.5μA. Compared with the wet gas generator containing PAN membrane and PVDF membrane, the current output of the wet gas generator containing only PAN membrane and only PVDF membrane is relatively low. Therefore, the presence of PAN diffusion layer and PVDF evaporation layer has a synergistic effect and obvious effect on the comprehensive output of the wet gas generator.
[0040] Figure 11-12 The output performance diagram of the wet gas generator using different electrode combinations is shown in Figure 2. Figure 11-12 It can be seen that the output performance of the wet gas generator using asymmetric electrodes composed of Al-C is the best. The reason is that the electrodes undergo redox reactions, which can continuously provide metal ions. Driven by moisture, the ions migrate from high-concentration areas to low-concentration areas. Due to the charge difference, the wet gas generator can generate electricity continuously.
[0041] The wet gas generator of the present invention adopts a metal organic framework MOF-303 with a porous, efficient moisture absorption and stable structure. The metal ions and organic ligands of MOF-303 are used to form a porous material. The rich micro-nano pore structure of MOF-303 enhances the adsorption of water molecules. BC is used as a carrier. BC has a unique woven structure and has high water absorption and high water retention due to the "nano effect". It has high permeability to liquids and gases, high wet strength, and an ultra-fine network structure. The high specific surface area of MOF-303 is combined with the nanostructure of BC to improve the moisture absorption capacity and efficiency. In the wet gas generator, MOF-303 and BC are composited and then impregnated with lithium chloride solution. The MOF-303 / BC / LiCl composite membrane is obtained by adding lithium chloride solution, which can enhance the moisture absorption capacity of the hygroscopic layer; the lithium chloride solution enhances the ion concentration difference, which can optimize the moisture transport path of the PAN / PVDF membrane. The PAN membrane and the PVDF membrane work synergistically to achieve the diffusion and evaporation of water molecules under the action of the gradually decreasing pore size of the PAN and PVDF fiber membranes, thereby achieving directional migration and evaporation of water; using asymmetric electrodes, the aluminum electrode and carbon paper form a redox reaction, drive ion migration, generate a continuous charge difference, and realize stable and continuous wet power generation; the sandwich structure packaging ensures the stability and environmental adaptability of the device, and can generate electricity in a wide humidity range (20-90%RH).
[0042] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a wet gas generator, characterized in that: The following steps are involved: Step 1: MOF-303 and bacterial cellulose BC were mixed in a mass ratio of 1:(5-11), and the first composite membrane was obtained by vacuum filtration and drying; Step 2: Immersing the first composite membrane in a lithium chloride solution with a concentration of 5-30%, and drying the solution after immersion to obtain a second composite membrane; Step 3: placing a polyacrylonitrile (PAN) membrane and a polyvinylidene fluoride (PVDF) membrane on the upper layer of the second composite membrane in sequence to obtain a third composite membrane; Step 4: placing the third composite membrane on a waterproof and breathable non-woven fabric, and combining it with an asymmetric electrode to form a sandwich structure, wherein the asymmetric electrode is an aluminum electrode as a cathode and carbon paper as an anode, and encapsulating to obtain a moisture generator.
2. The method for preparing a wet gas generator according to claim 1, characterized in that: The mass ratios of MOF-303 and BC in step 1 are 1:5, 1:7, 1:9, and 1:
11.
3. The method for preparing a wet gas generator according to claim 1, characterized in that: The mixing conditions in step 1 are: processing in a high-speed shearing machine with a rotation speed of 600-800 rpm; drying temperature of 60° C., and drying time of 30 min.
4. The method for preparing a wet gas generator according to claim 1, characterized in that: The concentration of the lithium chloride solution described in step 2 is 5%, 10%, 15%, 20%, and 30%.
5. The method for preparing a wet gas generator according to claim 1, characterized in that: In step 2, the first composite membrane is immersed in the lithium chloride solution for 30 minutes, and the drying temperature is 60° C. and the drying time is 30 minutes.
6. The method for preparing a wet gas generator according to claim 1, characterized in that: The fiber diameters of the PAN membrane and the PVDF membrane in step 3 are 500-2000 nm and are prepared by electrospinning.
7. The method for preparing a wet gas generator according to claim 1, characterized in that: The moisture generator formed after encapsulation with the waterproof and breathable non-woven fabric in step 4 can generate electricity stably within a humidity range of 20% to 90% RH.
8. A wet gas generator, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 7, comprising: The moisture absorption layer (1) is composed of a MOF-303 / BC / LiCl composite membrane; Diffusion layer (2), composed of PAN film; A moisture-wicking layer (3) composed of a PVDF membrane; an asymmetric electrode consisting of an aluminum electrode (4) and a carbon electrode (5); The moisture absorption layer (1), the diffusion layer (2), and the moisture discharge layer (3) are stacked in sequence and encapsulated by an asymmetric electrode and a waterproof and moisture-permeable non-woven fabric (6).
9. The wet gas generator according to claim 8, characterized in that: The loading amount of lithium chloride in the hygroscopic layer is 5-20% of the mass of the composite membrane after impregnation.
10. The wet gas generator according to claim 8, characterized in that: The moisture generator outputs different currents and voltages under different humidity conditions.